2017
DOI: 10.1111/bjso.12192
|View full text |Cite
|
Sign up to set email alerts
|

The sigh of the oppressed: The palliative effects of ideology are stronger for people living in highly unequal neighbourhoods

Abstract: Ideologies that legitimize status hierarchies are associated with increased well-being. However, which ideologies have 'palliative effects', why they have these effects, and whether these effects extend to low-status groups remain unresolved issues. This study aimed to address these issues by testing the effects of the ideology of Symbolic Prejudice on well-being among low- and high-status ethnic groups (4,519 Europeans and 1,091 Māori) nested within 1,437 regions in New Zealand. Results showed that Symbolic P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
54
2
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(72 citation statements)
references
References 93 publications
5
54
2
5
Order By: Relevance
“…For instance, Sengupta et al . () found a positive and significant relationship between endorsing legitimizing ideologies (i.e., symbolic prejudice) and psychological well‐being, but more importantly, this relationship was similar when comparing different ethnic groups rather than more prevalent in the dominant ethnic group. Quinn and Crocker (, study 2) on the other hand showed that the priming of a Protestant work ethic increased depression levels among overweight women (as a proxy of low status); this same effect could not be found among non‐overweight participants.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…For instance, Sengupta et al . () found a positive and significant relationship between endorsing legitimizing ideologies (i.e., symbolic prejudice) and psychological well‐being, but more importantly, this relationship was similar when comparing different ethnic groups rather than more prevalent in the dominant ethnic group. Quinn and Crocker (, study 2) on the other hand showed that the priming of a Protestant work ethic increased depression levels among overweight women (as a proxy of low status); this same effect could not be found among non‐overweight participants.…”
Section: Introductionmentioning
confidence: 94%
“…They found that the effect of symbolic prejudice, the variable used in their study to measure system justification ideology, was positively related to personal well‐being in a New Zealand sample. They hypothesized that symbolic prejudice is a legitimizing ideology, because low‐status groups ‘should not receive any systematic compensation for their poorer social outcomes’ (Sengupta et al ., , p. 4). More importantly, they showed that the relationship between symbolic prejudice and well‐being was stronger in highly unequal regions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings were broadly consistent with the notion derived from dissonance theory that those who suffer most intensely from a given state of affairs would be especially motivated to justify it (see also Henry & Saul, ; Sengupta, Osborne, & Sibley, ). A few studies have recently picked up on this idea, suggesting that the palliative effects of system justification may be stronger for the disadvantaged than the advantaged, at least under some circumstances (Sengupta, Greaves, Osborne, & Sibley, ; Vargas‐Salfate, ).…”
Section: Introductionmentioning
confidence: 99%